Banach-Mackey, locally complete spaces, and ℓp,q-summability - Carlos Bosch; Armando García (International Journal of Mathematics and Mathematical Sciences)
We defined the ℓp,q-summability property and study the relations between the ℓp,q-summability property, the Banach-Mackey spaces and the locally complete spaces.